To estimate the efficacy of 0.1% tacrolimus with Colgate Oraguard-B paste for the treatment of patients with symptomatic oral lichen planus - Nisa, Shams Ul (Indian J Dent, 2016)
AIM AND OBJECTIVES: To investigate the efficacy of 0.1% tacrolimus with Colgate Oraguard-B paste for the treatment of patients with oral lichen planus (OLP). MATERIALS AND METHODS: One hundred and fifty patients with symptomatic OLP participated in the study, who had clinically and histopathologically proven OLP. In this study, patients were provided with 0.1% tacrolimus ointment with Colgate Oraguard-B paste as the study medication. Patients were asked to use the medication over the areas three times a day until resolution of the lesion. Patients were recalled to assess the drug response every 15 days. The duration of treatment ranged from 3 months to 4 months, with follow-up of 2 years and 6 months. STATISTICAL ANALYSIS: The Wilcoxon signed-rank test was performed, which is a nonparametric statistical hypothesis test for comparing two related samples, matched samples or repeated measurements on a single sample to assess whether their population mean ranks differ (i.e., it is a paired difference test). In our study, the pre- and post-Visual Analogue Scale (VAS) values were compared and the mean, standard deviation and P values were calculated. RESULTS: Of 150 patients, 71 (47.33%) patients had complete resolution of the lesion to the topical tacrolimus therapy. Sixty-five (43.33%) patients had marked resolution of their lesions, i.e., the size of the lesion was decreased. Fourteen (9.33%) patients had remission of lesion (reduction in burning sensation and size of lesion) in symptoms as recorded by the VAS. CONCLUSION: Topical tacrolimus ointment 0.1% in Oraguard-B paste is an effective treatment for different types of OLP.